JURISPRUDENTIAL ASPECTS REGARDING THE APPLICATION OF THE NE BIS IN IDEM PRINCIPLE IN THE AREA OF FREEDOM, SECURITY AND JUSTICE WITHIN THE EUROPEAN UNION - Mihaela-Augustina DUMITRAȘCU; Oana-Mihaela SALOMIA (Challenges of the Knowledge Society)
The establishing of the Area of Freedom, Security and Justice represents one the main features which individualizes EU among other international intergovernmental organizations and it contributes to the integration of the Member States „with respect for fundamental rights and for the different legal systems and traditions of the Member States”. The Third Part of the Treaty on the functioning of the European Union, named „Area of Freedom, Security and Justice” (AFSJ), regulates the policies on border checks, asylum and immigration, judicial cooperation in civil matters, judicial cooperation in criminal matters and police cooperation which are covered by the shared competence of the Union with the Member States. As it is stated in the Treaty, this field is regulated at European level taking into account the national systems of law, including common law principles and „traditions” of the Member States; one of these principles is ne bis in idem provided for by different types of rules within the EU Law on: the Area of Freedom, Security and Justice, the Schengen Area, the European Arrest Warrant, the EPPO, and also the provisions of the Charter of Fundamental Rights of the European Union. These rules have been interpreted by the CJEU, which has established the content of the principle applied in the Area of Freedom, Security and Justice and, also, the conditions regarding the restrictions which could be brought to this principle. The analysis of the jurisprudential findings underlines that the interpretation made by the Court of Luxembourg is compulsory for the European institutions, the Member States and the citizens and also the companies, and it is pronounced with the respect of the limits of the EU competencies and in line with the ECtHR decisions.